Apoptotic effect of green synthesized Magnesium oxides nanoparticles (MgO) from Plumbago zeylanica Linn leaf extract against Breast cancer cell lines - jain, D Khushi; Ganesh.S , Balaji (Journal of Neonatal Surgery, 2024)
INTRODUCTION :Nanoparticles can be defined as objects ranging in size from 1- 100 nm. Magnesium oxide nanoparticles have unique properties such as biodegradability, non-toxicity, degradation of harmful dyes. Along with its easy synthesis it is widely applicable for toxic waste remediation, antibacterial materials, removal of industrial pollutants and also used in anti-arthritic and anti-cancer activities. Various reports state that the plant P. zeylanica consists of bioactive compounds which possess anti cancer activity. It also reveals that plumbagin can inhibit cell proliferation and induce apoptosis. AIM: To confirm the effect of apoptosis using green synthesis magnesium oxide nanoparticles from Plumbago zeylanica Linn leaf extract against breast cancer cell lines. MATERIALS & METHODS: Preparation of aqueous extract of P. zeylanica : The fruits were dried and powdered. The aqueous extract was prepared by adding 100 ml distilled water to 20gm of P.zeylanica powder . Synthesis of nanoparticles : Drops of Mg Nitrate are added to the extract on a magnetic stirrer. The mixture is centrifuged to obtain MgO nanoparticles. These nanoparticles are tested for UV,SEM, FTIR,XRD RESULTS: Green synthesis of magnesium oxide nanoparticles using Plumbago zeylanica Linn leaf extract was successfully confirmed by UV–Visible spectroscopy, FTIR, XRD, and SEM analyses. The synthesized MgO nanoparticles exhibited significant concentration-dependent cytotoxicity against MCF-7 breast cancer cells and induced apoptosis, as evidenced by reduced cell viability and characteristic apoptotic morphological changes (p < 0.05). CONCLUSION : The green synthesized magnesium oxide NP from p.zeylanica Linn leaf extract showed apoptotic effect against breast cancer cell lines. However, further research is needed to fully understand the synthesis mechanism, optimize the synthesis conditions and evaluate the stability and long term effects of Magnesium oxide nanoparticles synthesized using P.zeylanica extract